(x/1)-(4x/3)=-1

Simple and best practice solution for (x/1)-(4x/3)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x/1)-(4x/3)=-1 equation:



(x/1)-(4x/3)=-1
We move all terms to the left:
(x/1)-(4x/3)-(-1)=0
We add all the numbers together, and all the variables
(+x/1)-(+4x/3)-(-1)=0
We add all the numbers together, and all the variables
(+x/1)-(+4x/3)+1=0
We get rid of parentheses
x/1-4x/3+1=0
We calculate fractions
There is no solution for this equation

See similar equations:

| -4/5s=6 | | x-18/8=-7 | | 2(11t+1.5t)=12 | | (5x/8)+(x/12)=(51/24) | | 3x-(x-12)=4 | | 4(3x+6)-6(4x-7)=10x+3(4x-9) | | 20Xn=7000 | | X/4=20;x=5 | | y=-4-3+3 | | 20Xx=7000 | | 8/9=7/3x | | -4x+33+2x+81=135 | | 8x+2+4x+11=121 | | 54=6x-36 | | ^+6x=16 | | 3x-37=48 | | 3(7-1)+2(y+3=13 | | 2x+14.5=25.5 | | 6/4x+3/4=2 | | 24=4(4m-2) | | 11y/28-2=4-7y/4 | | 2.2(4p+2=13.2 | | -3x=12-5+11 | | -9g=-0.74-16.4g | | 25v+3(5v+3)-4(7v+1)=-88 | | 29x+-3=15x+7 | | X+3+8=2x+4 | | (4)/(3)=(x)/(56) | | -8-15-18k=-11k+19 | | 1/5(n-10)=6-3.5 | | 4x+10+x+20=30 | | |8x-5|=-21 |

Equations solver categories